The Dynamics of the Evolution of Islamic Law from the Prophetic Era to the Abbasid Dynasty: A Historical–Normative Analysis of Revelation, Ijtihad, and Power - Ismasnawati; Kamal, Tamrin; Saifullah; Asmaret, Desi; Julhadi (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2025)
This study examines the dynamics of the evolution of Islamic law from the period of the Prophet Muhammad to the Abbasid Dynasty, focusing on the interaction between revelation, ijtihad, and political authority. This research employs normative legal research with historical and conceptual approaches, relying on library research of classical and contemporary Islamic legal sources. The findings indicate that Islamic law developed dynamically in response to shifting social, political, and cultural contexts across historical periods. During the Prophet’s lifetime, Islamic law evolved through revelation that addressed concrete social realities. In the era of the Companions, ijtihad emerged as a primary legal mechanism to address new legal challenges following the Prophet’s death. Furthermore, during the Umayyad and Abbasid periods, political authority and territorial expansion played a significant role in shaping the institutionalization and codification of Islamic law, culminating in the formation of major schools of Islamic jurisprudence. This study argues that the adaptability of Islamic law, facilitated by ijtihad, constitutes its foundational strength in responding to historical change